Land use change and its relation to land allocation : a case study of Namon and Houiayang, Longxane district, Xaysomboun special zone, Lao PDR - Khamla Phanvilay; Apisit Eiumnoh; Lantican, Celso B.; Remigio, Amador R.; Routray, Jayant Kumar; Deutsche Gesellschaft filr Technische Zusammenarbeit (GTZ) (Bangkok : Asian Institute of Technology, 1996)
Land use change might indicate and help to predict future use ofland and other natural resources especially forest resources. In Laos, as a small countly, the maj01ity of people are still engaged in agriculture in which land use and farming system are considerably undeveloped. Rice is a major and predominant staple crop and about 40% of its production is from shifting cultivation in the upland area in which mainly practiced by min01ity groups who scattedng settle through out the countly. Present yield per unit area is considerably low, meanwhile the demand for staple food grain is increasing, to meet this demand the production has been increased th.rough the expansion of agricultural areas which the additional area comes from encroachment on natural forest resources. In this study, land use changes have been investigated through the use of ae1ial photo, satellite image1y, and field obse1vation in 1981, 1992, and 1996 respectively, in order to compare the land use and land covers in different time frames. Apa1t from this, socio-economic data were collected in order to supplement and supp01t on evidence of the land use change. Factors that deal with land use and land allocation such as government policies, productive systems were also included in the study and analysis. Two communities were selected to be a representative case. Tue first community is Lao loum who are a majodty, occupied lowland area or practicing paddy field cultivation that is considered as pe1manent agdculture. Tue second community is Lao Soung or Hmong who is considered as a minority group and occupied upland and highland and have skill in practicing shifting cultivation or tempora1y occupation. Migration and land secwity or tenural right are the major factors that this study puts emphasis on.
Thesis (M. Sc.) - Asian Institute of Technology, 1996
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Science, School of Environment, Resources and Development
Keywords: Land use -- Laos